Prevalence of oral health status and needs in institutionlized physically challenged children - Rahul Mishra; Atul Kumar Singh; Sanjana Tyagi; Harsha Vardhan Choudhary; Shweta Kirti Gupta; Kunal Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Oral hygiene has significant effect on the overall health of an individual as it has vital role in human life, so it is necessary to protect oral hygiene of all children since childhood. Objectives: The objectives were to evaluate and compare the prevalence of dental caries and oral hygiene status in institutionalized physically challenged children of Bihar. Materials and Methodology: A total of 700 (400 male and 300 female) children were included in the study that were physically handicapped and were institutionalized in various special schools. In this study, complete oral examination was done and was recorded by using Oral Hygiene Status-Simplified given by Greene and Vermillion, 1964, and all statistical analyses were done by using SPSS software. For statistical analysis, Chi-square test and ANOVA were used. Results: Out of 700 children, 48.8% (342) had dental caries with mean Decayed, Missing, and Filled Teeth (DMFT) index of 0.86 (standard deviation [SD] ±1.37) and mean dmft index of 0.36 (SD ± 0.98). In this study, orthopedic, blind, deaf and dumb, and compound students were examined. It was observed that the dental caries prevalence was high in the blind group (71%) compared to that of the deaf and dumb group (40.2%), while oral hygiene status was observed as good in 42.2%, fair in 46.9%, and poor in 10.9% of children. Conclusion: Every dental professional should be aware of his/her responsibilities and provide both comprehensive and incremental dental care to improve the overall oral hygiene condition of physically handicapped children.